New media, lifestyle transformation, and public health: unraveling the digital divide in China - Ma, Ruize; Zheng, Tenglong; Wang, Mengxin; Gu, Jiasheng (Frontiers in Public Health, 2025)
New media has profoundly reshaped everyday life in China, particularly influencing leisure lifestyles and raising new public health concerns. As the use of new media continues to rise, its impact on social behavior and well-being has become an urgent area of study. This study uses data from the 2018 Chinese General Social Survey (CGSS) and employs factor analysis and Oaxaca-Blinder decomposition to assess the impact of new media usage on lifestyle diversity across different social groups. The analysis focuses on various aspects of leisure activities and time use. Our findings show that increased use of new media promotes social leisure activities but leads to a reduction in participation in cultural and entertainment activities. Furthermore, lifestyle diversity is significantly lower among frequent new media users, with 50.7% of the disparity in lifestyle diversity attributed to the digital divide. This study suggests that while new media facilitates social interaction, it also fragments time use and may have negative consequences for mental well-being and social richness. To address these issues, policy responses should aim to reduce the digital divide and balance digital engagement with the need for diverse and healthy leisure activities, promoting both social connection and mental health.